A Possible Role of Polycystic Ovary Syndrome for Pregnancy Complications in Women with Psoriasis. (November 2014) - De Simone, Clara; Caldarola, Giacomo; Corbeddu, Marialuisa; Moro, Francesca; Tropea, Anna; Moretta, Gaia; Apa, Rosanna
Abstract: Postmarketing Phase IV Psoriasis is a common, chronic, relapsing immune‐mediated inflammatory disease (IMID) of the skin. IMIDs are multifactorial diseases characterized by common molecular pathways leading to a systemic inflammation. Patients with an IMID are also at higher risk of developing co‐morbidities, such as adverse pregnancy outcomes, than the general population. A higher rate of pregnancy complications have been seen in inflammatory bowel disease and rheumatoid arthritis. The data for psoriasis are inconsistent but it appears that women with moderate‐to‐severe psoriasis may also have an increased risk of poor pregnancy outcomes. The cause of this association is unknown, although it may be related to elevated proinflammatory cytokines such as IL‐6 and TNF‐α, the high prevalence of comorbidities and other unhealthy behaviours, or the high prevalence of polycystic ovary syndrome (PCOS). In a recent study, PCOS prevalence in a psoriatic cohort ( n  = 51) was higher than in non‐psoriatic women ( n  = 102) (47% versus 11%), and women with PCOS and psoriasis had a greater probability of insulin resistance, hyperinsulinaemia, and dyslipidaemia as well as a more severe skin condition, than those with psoriasis alone. Further studies are necessary to clarify the impact of psoriasis on pregnancy and in particular if these effects are mediated by concomitant PCOS.